1999
DOI: 10.1101/lm.6.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Landmark Discrimination Learning in the Dog

Abstract: Allocentric spatial memory was studied in dogs of varying ages and sources using a landmark discrimination task. The primary goal of this study was to develop a protocol to test landmark discrimination learning in the dog. Using a modified version of a landmark test developed for use in monkeys, we successfully trained dogs to make a spatial discrimination on the basis of the position of a visual landmark relative to two identical discriminanda. Task performance decreased, however, as the distance between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(11 citation statements)
references
References 17 publications
1
9
1
Order By: Relevance
“…Both chimpanzees and rhesus monkeys are not able to find the hidden food in a Wisconsin task if the signalling marker object ("beacon") is placed more than 20 cm away from the actual location (Jenkins, 1943;Murphy & Miller, 1955). Similar observations were reported for dogs in asocial situations (Milgram et al, 1999). Further, many other species tested are able to learn easily in delayed matchingto-sample tasks but still cannot learn to choose correctly in an object choice task if they have to choose on the basis of a momentary pointing gesture (i.e.…”
Section: Discussionsupporting
confidence: 56%
“…Both chimpanzees and rhesus monkeys are not able to find the hidden food in a Wisconsin task if the signalling marker object ("beacon") is placed more than 20 cm away from the actual location (Jenkins, 1943;Murphy & Miller, 1955). Similar observations were reported for dogs in asocial situations (Milgram et al, 1999). Further, many other species tested are able to learn easily in delayed matchingto-sample tasks but still cannot learn to choose correctly in an object choice task if they have to choose on the basis of a momentary pointing gesture (i.e.…”
Section: Discussionsupporting
confidence: 56%
“…In the current study, I investigated the metric properties of landmark-based search memory in the domestic dog. Although recent studies revealed that dogs can use landmark information to locate a disappearing object (Fiset, Gagnon, & Beaulieu, 2000; Fiset, Beaulieu, Leblanc, & Dubé, in press) or discriminate a spatial position (Milgram et al, 1999; Milgram et al, 2002), how they encode and use spatial information provided by the landmarks is unclear. Furthermore, most of the studies that have investigated the metric properties of landmark-based search memory in animals have used avian species with a few exceptions, such as bees (Cartwright & Collett, 1987; Cheng, Collett, Pickhard, & Wehner, 1987; Collett & Kelber, 1988), gerbils (Collett et al, 1986), humans (Spetch, 1995; Spetch et al, 1996; Spetch et al, 1997), marmoset monkeys (MacDonald, Spetch, Kelly, & Cheng, 2004) and squirrel monkeys (Sutton, Olthof, & Roberts, 2000).…”
mentioning
confidence: 99%
“…However, an alternative explanation also is possible. Although dogs have proved to be able to use both egocentric and allocentric cues in spatial tasks (Milgram et al, 1999), it is still possible that in this study dogs coded the searched location prevalently egocentrically rather than in relation to other landmarks in the testing room. In fact, the particular constraints used in the experiments to determine the locations used in each discrimination determined that only Condition A– B+ featured a reversal of the reward consistencies in respect to the left or the right of the animal approaching the pair of containers, it is possible that only this condition was affected by a negative transfer of learning.…”
Section: Methodsmentioning
confidence: 86%